SPATIAL PLANNING BASED ON LOCAL WISDOM IN THE SAMBORI INDIGENOUS COMMUNITY THROUGH MANAGEMENT OF ETNO TOURISM POTENTIAL - Suriadi Ardiansyah; Enok Maryani (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2022)
The development of the population, which is accompanied by an increase in human needs invarious aspects, causes various spatial problems. Spatial problems include settlements andunhealthy community environments such as slums, prone to floods, droughts, fires, pollution anddamage to the environment, joblessness, and the spread of various diseases. Therefore, it isnecessary to have a spatial arrangement that is in accordance with the needs and capacity of thespace, so that a beautiful, cool and harmonious life can be achieved. Basically, the concept ofspatial planning, ideally, has long been known by elements of Indonesian society, even beforethe explosion of population growth that occurs today. The existence of sacred spaces, areas, andland that are not allowed to build houses, residential areas in groups, areas for graves, areas forroads, areas for places of worship, agricultural areas, are forms of local spatial planning knownto the general public. Local wisdom is one of the community's capital to combine aspects ofnature conservation with aspects of economic fulfillment which is conceptualized as Ethnotourism. One of the potentials that many regions have in Indonesia is the natural potential whichbecause of its beauty and uniqueness can be developed for Ethno tourism. A very closecorrelation between local wisdom and ecotourism is that the local wisdom of a particularcommunity is usually related to the way it relates to the environment and the naturalsurroundings. The interaction of this wisdom is a very good attraction to be packaged into aunique ecotourism concept. Based on the conceptual description of the analysis and the empiricalconditions. It seems that the implementation of local spatial planning is one of the mostfundamental alternatives to be presented in a scientific format so that we can understand moredeeply the spatial concept built by our ancestors. Moreover, in the era of globalization whichpresents a very strong influence on all dimensions of life, including spatial planning, thusrequiring us to have a strong foundation in managing space as a place to live and develop. This iswhere local values in managing spatial planning are needed to strengthen the identity andindependence of the Indonesian nation. One of the villages in the Bima Regency that is able tomaintain the traditions and local values of the Indonesian people's spatial planning is theSambori Traditional Village community. The Sambori community has used a spatial plan that isvery in line with the values and spatial patterns in ecotourism management that is rational and inaccordance with its ideal designation.